Ab initio modelling of helium behavior in α-Fe/TaC interface. (June 2021) - Sun, Dan; Li, Ruihuan; Yang, Yaochun; Ding, Jianhua; Zhang, Pengbo; Zhao, Jijun
Highlights: Ta13 C14 @Fe215 and {1 0 0} 〈1 1 0〉 Fe//{1 0 0} 〈1 0 0〉 TaC interface models are built. He atoms are easier to aggregate and diffuse at interface than that in matrix. Cr atoms occupying the Fe site is more stable than Fe vacancies at the interface. Abstract: To understand the role of α-Fe/TaC interface on the clustering behavior of helium (He) atoms inside castable nanostructured alloys under irradiation, we built two models (Ta13 C14 @Fe215 and {1 0 0} 〈1 1 0〉 Fe//{1 0 0} 〈1 0 0〉 TaC interface) and perform systemical ab initio calculations to investigate the energetics of point defects (vacancy, anti-site defect and He), substitutional defect clusters CrFem (1 ≤ m ≤ 4), and Hen (1 ≤ n ≤ 4) clusters, the migration behavior of He atom as well as the effect of Cr atoms and vacancies on the stability of Hen clusters. Vacancy and He at the α-Fe/TaC interface of the Ta13 C14 @Fe215 are more stable than that in Ta13 C14 cluster and Fe matrix. Ta atom at this interface escapes from the lattice site more easily than C atom. In addition, the Cr atoms substituting Fe sites are more stable than Fe vacancies, which reduces the formation energies of Hen clusters in α-Fe/TaC on the Ta13 C14 @Fe215 . Both formation energy and migration energy of He atom in {1 0 0} 〈1 1 0〉 Fe//{1 0 0} 〈1 0 0〉 TaC interface are lower than those in bulk TaC and α-Fe. Hence, {1 0 0} 〈1 1 0〉 Fe//{1 0 0} 〈1 0 0〉 TaC interface as a sink can trap more helium atoms and vacancies than α-Fe matrix.